The Black Church as a caring community for the poor: Southern Synod as investigative centre - L. Modise (Acta Theologica)
In this article, the researcher discusses first the Black Church in relation to God, one another, and the world and, secondly, the blackness of the URCSA reflected in terms of her membership’s pigmentation and her identity of the Black church. Thirdly, the author illustrates why a Black theology of liberation is needed in the post-apartheid era in terms of the poverty level in South Africa. On average, 4.35% of Whites are poor in comparison to 61.4% of poor Black African people. Finally, the author focuses on how the Black church should be a caring community for the poor, destitute, oppressed and wronged in both church and society.